2018
DOI: 10.17679/inuefd.336272
|View full text |Cite
|
Sign up to set email alerts
|

Ergenlerde Dijital Oyun Bağımlılığı ve Psikolojik İhtiyaçlar

Abstract: The importance of the internet and virtual platform in human life gradually has been increasing with the help of improving technology. It has been thought that this subject should be dealt with; because inappropriate use of the internet and computer games can turn into the risk of addiction. The psychological needs of teenagers which predict the addiction of digital games has been studied in this research. 322 teenagers comprise the research sample. "Personal Information Form", "The Scale of Digital Game Addic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 27 publications
2
4
0
9
Order By: Relevance
“…When relevant studies are examined, although some researchers suggest that there is no significant difference between male and female gaming addiction (Colwell et al, 1995;Kim et al, 2008), other studies have consistently shown that males are more likely to experience problematic gaming and gaming addiction (Bonanno & Kommers, 2005;Ekinci et al, 2019;Greenberg et al, 2008;Kanat, 2019;Phillips et al, 1995;Saunders et al, 2017). The possible explanation for these findings are that men are heavier game users than women, gaming is perceived as male activity (Bonanno & Kommers, 2005;Fox & Tang, 2014;Kanat, 2019;Lopez-Fernandez et al, 2019), men are more impulsive (Ahrends, 2017), and based on selfdetermination theory, gaming offers the possibility to satisfy basic human needs such as autonomy and competence, particularly among men (Dursun & Capan, 2018;Reinecke et al, 2012). However, Lopez-Fernandez et al (2019) note that although gaming addiction studies generally focus on male gamers, there is an increasing number of female gamers.…”
Section: Discussionmentioning
confidence: 98%
“…When relevant studies are examined, although some researchers suggest that there is no significant difference between male and female gaming addiction (Colwell et al, 1995;Kim et al, 2008), other studies have consistently shown that males are more likely to experience problematic gaming and gaming addiction (Bonanno & Kommers, 2005;Ekinci et al, 2019;Greenberg et al, 2008;Kanat, 2019;Phillips et al, 1995;Saunders et al, 2017). The possible explanation for these findings are that men are heavier game users than women, gaming is perceived as male activity (Bonanno & Kommers, 2005;Fox & Tang, 2014;Kanat, 2019;Lopez-Fernandez et al, 2019), men are more impulsive (Ahrends, 2017), and based on selfdetermination theory, gaming offers the possibility to satisfy basic human needs such as autonomy and competence, particularly among men (Dursun & Capan, 2018;Reinecke et al, 2012). However, Lopez-Fernandez et al (2019) note that although gaming addiction studies generally focus on male gamers, there is an increasing number of female gamers.…”
Section: Discussionmentioning
confidence: 98%
“…Erkek öğrencilerin bağımlılık puan ortalamaları kadın öğrencilere göre daha yüksektir. Bu sonuç yapılan diğer araştırma sonuçlarıyla örtüşmektedir (Bekir, 2018;Çakır, Ayas, & Horzum, 2011;Dursun & Eraslan Çapan, 2018;Göldağ, 2018;Kurtbeyoğlu, 2018;Odabaşı, 2016;Tekindal & Çalışkan, 2016). Gelir durumuna göre çevrimiçi oyun bağımlılığı seviyesi artmaktadır.…”
Section: Tablo 5 Saldırganlığın Demografik Değişkenlere Göre Farklılunclassified
“…Gençler tarafından bilgisayar, cep telefonu ve oyun konsolu gibi teknolojik aygıtlar ve yazılımlar sayesinde birçok katılımcının beraber oynayabileceği sanal ortama aktarılmış olan çevrimiçi oyunlar yoğun olarak tercih edilmektedir (Dursun & Çapan, 2018). Günümüz çağında teknolojik gelişmeler sonucunda akıllı telefonlar aracılığıyla da oyun kullanıcıları küresel müsabakalar yapabilmektedir.…”
Section: Introductionunclassified
“…DiB kavramı (21)(22)(23)(24), teknoloji bağımlılığı (25), internet bağımlılığı (26), sosyal ağlarda DiB (4) gibi konularda yapılan çalışmalar mevcuttur. Ülkemizde oyun bağımlılığı üzerine yapılan çalışmalar; oyun bağımlılığının farklı yaş gruplarına olan etkisi (27)(28)(29)(30)(31), psikolojik faktörler (32)(33)(34)(35)(36)(37) ve sporun etkisi (38,39) gibi konuları kapsamaktadır. Ayrıca son yıllarda teknoloji bağımlılığı, internet bağımlılığı, sosyal medya bağımlılığı, akıllı telefon bağımlılığı ve dijital oyun bağımlılığı gibi bağımlılık türlerini, farklı bağımlılık türleri ile araştıran çalışmalar artış göstermiştir (40)(41)(42)(43)(44).…”
Section: Introductionunclassified